One text, many stories: The (ir)relevance of reader-response criticism for apocryphal literature in the Septuagint - S. Philip Nolte (HTS Teologiese Studies/Theological Studies, 2012)
This article investigated the value of reader-response theory for the reading of apocryphal texts in the Septuagint. The groundbreaking work on reader-response theory developed by Wolfgang Iser in his book The Act of Reading: A Theory of Aesthetic Response, written in 1978 served as the theoretical point of departure. Although the reader-response theory has been scrutinised and criticised heavily during the last three decades, Iser made a very valuable contribution to the reading of literature. My assumption is that religious texts have to be read in the same way as other literature and therefore literary theories such as Iser’s can be conducive for responsible interpretation. The article consists of the following parts: introductory remarks on the value of reader-response theory for the interpretation of apocryphal texts; a short overview of reader-response criticism; a discussion and evaluation of three different aspects of Iser’s theory, namely ‘gaps’ in texts, ‘asymmetry’ between readers and texts and the concept of ‘the implied reader’. The findings of the investigation will be given in part five (Findings).